An Analysis of the Effects of People’s Intention to Pay Zakat in Zakat Institutions - Fadhillah, Syahrur; Pudjihardjo, M (Islamic Economics and finance in Focus, 2026)
This research aims to determine the influence of performance accountability, reporting transparency, and guarantee of data privacy protection on the interest of the people of Malang City in paying zakat through zakat amil institution. The method used is quantitative using logistic regression analysis. The data used is primary data with 200 respondents who are residents in Malang, Muslim, and they are able to pay zakat independently. The result show that the performance accountability and reporting transparency variables have a partially significant influence, while the guarantee data privacy protection variable does not have a partial significant influence on the interest of the people of Malang City in making zakat payments through zakat amil institutions. It is hoped that the result of the research can become a reference so that amil zakat institutions continue to improve the quality and services of their agencies so that the people of Malang City become more enthusiastic in paying zakat through amil zakat institutions.